The clinical and pathological features of patients with gastric cancer in Turkey: A Turkish Oncology Group Study - Yalçin, Bülent; Zengin, Nurullah; Aydin, Fazil; Ilhan, Mahmut; Işikdo?an, Abdurrahman; Demir, Gökhan; Içli, Fikri (My University, 2006)
Although the incidence of gastric cancer has declined dramatically in western countries; it is, after the breast cancer in women and lung cancer in men, the second most common cancer in Turkey with a high mortality. Surgery is the mainstay in the management of gastric cancer, and unresectable disease has poor prognosis. The aim of this study was to evaluate the clinicopathological and epidemiological features of patients with gastric cancer in Turkey. A questionnaire was used to collect information on clinicopathological and socioeconomic features of all patients with newly diagnosed gastric cancer in contributing 16 different centers in Turkey in the year 2004. The findings were analyzed by the geographic regions in patients live. Nine-hundred seventy-one patients with newly diagnosed gastric cancer in 2004 were included in the study. Mean age of the patients was 57±12.9 (mean±SD) years. Male-female ratio was 2/1. The rate of cancer resectability was lower in Eastern Turkey (ET) than Western Turkey (WT) (31.6% vs. 63.4%, p=0.0001). Also, socioeconomic status of the patients was lowest in ET (53.6% vs. 32.3%, p=0.0001). H. pylori gastritis and intestinal metaplasia were more common in ET when compared to WT (75.0% vs. 40.5%; p=0.003, and 68.4% vs. 18.1%; p=0.0001, respectively). Lower resectability rate of disease in ET should be appreciated. Further epidemiological study of gastric cancer is warranted in Turkey.
Keywords: Gastric cancer; Helicobacter pylori; Resectability